1997
DOI: 10.1042/bj3220135
|View full text |Cite
|
Sign up to set email alerts
|

The CD46 transmembrane domain is required for efficient formation of measles-virus-mediated syncytium

Abstract: Two phosphatidylinositol (PI)-anchored versions of a measles virus (MV) receptor membrane cofactor protein (MCP; CD46) were generated by fusing the extracellular domain of MCP to the decay-accelerating factor (DAF; CD55) or its PI anchor. The PI-anchored forms of MCP expressed on Chinese hamster ovary cells, otherwise non-permissive to MV, conferred a smaller MV cytopathic effect than a wild-type MCP, a Ser/Thr-rich domain-deletion mutant and a cytoplasmic tail-deletion mutant of MCP. Therefore the differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Additionally, employing a mouse macrophage cell line transfected with human MCP, Hirano et al observed changes in NO production following stimulation with IFN-␥ that were related to which tail of MCP was expressed (46). Finally, intracellular domains were a critical factor for effective virus-cell fusion and subsequent MV replication (47,48), again suggesting the possibility of a signal transducing event mediated by MCP.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, employing a mouse macrophage cell line transfected with human MCP, Hirano et al observed changes in NO production following stimulation with IFN-␥ that were related to which tail of MCP was expressed (46). Finally, intracellular domains were a critical factor for effective virus-cell fusion and subsequent MV replication (47,48), again suggesting the possibility of a signal transducing event mediated by MCP.…”
Section: Discussionmentioning
confidence: 99%
“…In many systems tested, CD46 has been demonstrated to mediate this process (Seya et al, 1997;Mori et al, 2003). Albright and colleagues have shown that human adult oligodendrocytes, as well as microglial cells, can be infected when cultured together with HHV-6-infected lymphocytes and that this process results in the formation of multinucleated cells.…”
Section: Introductionmentioning
confidence: 96%
“…Cells with high expression levels were screened through FACS Vantage using MV-H mAb as a marker. These cells were additionally transfected with MV-F cDNA in some experiments (38). Cells were cultured for 48 h at 37°C in RPMI 1640/10% FCS.…”
Section: Expression Of Mv-h Mutants On Mel Cells and Coculture Assay mentioning
confidence: 99%
“…Various rodent cells (39) were transfected with the MV-H cDNA of NV, those with V451A or I473L single mutations or that of KO using Lipofectamine (38). Vector only was used as the control.…”
Section: Expression Of Mv-h Mutants On Mel Cells and Coculture Assay mentioning
confidence: 99%
See 1 more Smart Citation